Os seus serviços públicos e políticos estão de certo modo ligados à prosperidade do município”: constituindo redes e consolidando o poder: uma elite política local (São Sebastião do Caí, 1875-1900) - Martiny, Carina (Universidade do Vale do Rio do Sinos, 2010)
The creation of the county of São Sebastião do Caí, in 1875, implied the structuration of a bureaucratic-administrative device and the political action of the local elite which began to take the places of power in the newly-founded City Council. Starting with the first county election that took place in São Sebastião do Caí, this Dissertation presents, firstly, the conditions that helped the political emancipation of São Sebastião do Caí, highlighting the economic dynamism developed from the exportation of the exceedance to the Province capital, the demographic growth derivated from the immigratory process – Germans as well as Italians – and the local leaderships’ want to enlarge the decision powers. The analysis emphasizes the political disputes between local factions, identifying the existence of a local elite preceding the very foundation of the county, as well as the role played by the City Council in the juncture of political transition from the Empire to the Republic. Secondly, attention is paid to the
Keywords: câmara municipal; prosopografia; redes; São Sebastião do Caí; elite política municipal; city council; prosopography; webs; county political elite; Ciências Humanas